A chilling reminder: Pediatric facial trauma from recreational winter activities. (August 2016) - Svider, Peter F.; Bobian, Michael; Hojjat, Houmehr; Sheyn, Anthony; Zuliani, Giancarlo; Eloy, Jean Anderson; Folbe, Adam J.
Abstract: Background: Winter activities offer children and adolescents an outdoor recreational opportunity during the coldest months. Our objectives were to estimate the national incidence of facial injury associated with recreational winter activities. Furthermore, we analyze demographic trends and clinical characteristics of patients presenting to emergency departments (EDs). Methods: The National Electronic Injury Surveillance System (NEISS), a population-based resource, was evaluated for ED visits from 2010 to 2014 for children injured from "active" winter –undertakings (snowboarding, skiing, ice skating) and sledding/tubing. Entry narratives were evaluated for demographics, diagnoses, and other clinical factors. Results: 841 entries amounting to an estimated 27, 618 patients were evaluated. The most common injuries were lacerations (69.4%), contusions/abrasions (19.5%), and fractures (5.5%), with the most common fracture sites being the nose (60.9%), orbit (15.2%), and mandible (10.9%). Median age was 9 years (IQR 5–12), and 65.8% were male. A greater proportion of adolescents sustained fractures than younger children (8.1% vs. 4.0%). The majority of fractures were to the nose. Conclusion: With nearly 30, 000 ED visits over five years, participation in winter sports can be perilous. Adolescents harbor a greater risk of sustaining serious injuries than younger children, and patients injured sledding/tubing had a greater fracture risk compared to those participating in more "active" winter activities. As upper/mid-face fractures occurred in only 1.4%, these findings reinforce a very limited role for CT. These findings suggest a need for greater use of facial protection and closer supervision of older children participating in these activities.